Modeling of Modified Value-At-Risk for the Skewed Student-T Distribution - Yuyun Hidayat, Sukono, Wahyuddin, Nunung Nurhasanah, Jumadil Saputra, (Opción, 2019)
This paper discusses the modeling of Modified Value-at-Risk(MVaR) for asset returns of skewed Student-T distribution. MVaRfor skewed Student-T distribution is a special form of MVaR models of nonnormal distribution. As a result, this model can beused to determine the amount of market risk. Student-T distributionis, especially used for asset returns. In conclusion, the performanceof each model Value-at-Risk applied in accordance with thedistribution of stock returns is quite good. It is shown that thevalues of QPS are in the interval [0, 2], and tend to be close to zero.